Pengaruh Pemasaran Relasional Kepercayaan Pelanggan terhadap Kepuasan Pelanggan (Studi pada 2A Computerizer Embroidery) - Rizka Fajrina S.; Engga Jalaludin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of relational marketing and customer trust on customer satisfaction at 2A Computer Embroidery. This type of research is quantitative research using SPSS version 17.0 analysis. The sampling technique used in this study is non-probability sampling, namely subjective sampling by the researcher and the respondents in this study were 2A Computer Embroidery customers. The results of this study indicate that: a). Relationship marketing has an effect on customer satisfaction of 6.1%. b). Customer trust has an effect on customer satisfaction by 23.6%. Relational marketing, and customer trust together have an effect on customer satisfaction by 28.6%.